1993
DOI: 10.1029/92wr02304
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for quantifying and valuing the impacts of flow changes on a fishery

Abstract: A quasi-population model for adult brown trout was developed for the Taylor River below the Taylor Park Reservoir in Colorado. This model allows the population to be predicted under alternative flow management regimes. The predicted population effects of two different flow release patterns were compared with the predicted population for the current reservoir operation regime. Changes in angler catch were imputed for these scenarios. The changes in catch were valued using estimates of willingness to pay obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In this case, anglers would answer yes or no to whether they would be willing to pay the stated dollar amounts for changes in daily catch rates and catch size of trout in Colorado. Harpman et al (1993) used the dichotomous choice CVM to estimate anglers' WTP for increases in average catch rate of trout in Colorado. Dichotomous choice CVM poses dichotomous questions to survey respondents, e.g.…”
Section: Valuation Techniquementioning
confidence: 99%
“…In this case, anglers would answer yes or no to whether they would be willing to pay the stated dollar amounts for changes in daily catch rates and catch size of trout in Colorado. Harpman et al (1993) used the dichotomous choice CVM to estimate anglers' WTP for increases in average catch rate of trout in Colorado. Dichotomous choice CVM poses dichotomous questions to survey respondents, e.g.…”
Section: Valuation Techniquementioning
confidence: 99%
“…Johnson (1989) found the marginal economic benefit to anglers for catching one additional fish to be $1.11 and the marginal value of a tenth additional fish was $0.46. Harpman et al (1993) studied trout fishing on the Taylor River in Colorado. Four hypothetical scenarios with different catch rates were described to mail survey respondents.…”
Section: Cvm Studies Estimating the Value Of Trout Fishingmentioning
confidence: 99%
“…A dichotomous-choice CVM approach was used. Results of Harpman et al (1993) indicated the marginal economic benefit of increasing catch per day by two fish to be $1.89 per fish. Using these benefit estimates, Johnson et al (1995) concluded that stocking catchable rainbow trout in Colorado needed to be reduced.…”
Section: Cvm Studies Estimating the Value Of Trout Fishingmentioning
confidence: 99%
“…More recently, Harpman et al (1993) used an extended version of IFIMnamely, the effective habitat model -to simulate the impact of two regimes of operation of Taylor Park Reservoir on fish population in Colorado. Their results predicted improvement in habitat conditions due to the operational strategy in place.…”
Section: Habitat Rating Methodsmentioning
confidence: 99%